The Unsettled Agreement of the 2019 Re-Demarcation of the Indonesia-Malaysia Boundary Line’s Impact - Nurdin, Amin; Sudjito, Sudjito; Arsana, I Made Andi (International Journal Labs, 2023)
Referring to the principle of uti possidetis juris, the establishment of the boundary line on Sebatik Island was based on a previous agreement between the Netherlands and the British. It was stated in the 1915 Agreement between the Netherlands and the British, which declared that the boundary line follows a parallel line of 4º10' North Latitude. Unfortunately, The Boundary Agreement of 1915 does not mention the datum and reference ellipsoid used to determine the abovementioned 4° 10' North Latitude. The absence of a datum and reference ellipsoid causes disputes in determining the precise location of boundary pillars during the field reconstruction procedure. A joint survey between Indonesia and Malaysia in 1983 found that most of the boundary pillars on Sebatik Island were not precisely located along the 4° 10' North Latitude line and based on the results of the 10th meeting of the Joint Working Group on the Outstanding Boundary Problems in 2018, Indonesia and Malaysia agreed to re-demarcate the boundary, which was carried out in 2019. This study aims to determine the impact of the 2019 re-demarcation of the boundary line between Indonesia and Malaysia on Sebatik Island. The methods applied in this research are in-depth interviews, observation, and document studies. The results found that the 2019 re-demarcation resulted in exchanging areas between Indonesia and Malaysia. This area exchange generates uncertainty about land ownership by citizens in border zones.